Preface special issue: “Processes and patterns in tropical hydrology” - Birkel Dostal, Christian (2023)
This SI aims at bringing together the state of the art in hydrological sciences of the Tropics derived from observed data, modelling, and hydrological theory, to critically outline the challenges and opportunities in tropical hydrology research. Because of greater energy inputs, larger atmospheric moisture recycling and faster rates of hydroclimatic change (including human-induced landscape and biogeochemical changes), hydrological processes and patterns in the Tropics differ from those in other hydroclimatic regions (e.g., Wohl et al., 2012). Yet, the lack of research infrastructure and funding in most tropical countries has to date precluded a more thorough understanding of hydrological processes in these highly dynamic systems. To improve hydrological predictions in this rapidly changing region, which is closely connected to and impacts the Extra Tropics (e.g., Liu et al., 2023), it is fundamental to gain new insight into the interplay between time-invariant catchment physical properties and time-variant controls on hydro logical processes.